If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -9) + 14 = (3x + -8) Reorder the terms: (-9 + 2x) + 14 = (3x + -8) Remove parenthesis around (-9 + 2x) -9 + 2x + 14 = (3x + -8) Reorder the terms: -9 + 14 + 2x = (3x + -8) Combine like terms: -9 + 14 = 5 5 + 2x = (3x + -8) Reorder the terms: 5 + 2x = (-8 + 3x) Remove parenthesis around (-8 + 3x) 5 + 2x = -8 + 3x Solving 5 + 2x = -8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 2x + -3x = -8 + 3x + -3x Combine like terms: 2x + -3x = -1x 5 + -1x = -8 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + -1x = -8 + 0 5 + -1x = -8 Add '-5' to each side of the equation. 5 + -5 + -1x = -8 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -8 + -5 -1x = -8 + -5 Combine like terms: -8 + -5 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 7X=10X | | 12=2(x+1)-6 | | 3(3x-3)-2=5x-43 | | 2x+1/8=5/3 | | 4(x+3)=2x+46 | | -1/4+1= | | 12+2x=42 | | -2.9c=8.7 | | -7=5(4x+3)-2 | | -8x-6=-6x-12 | | y=-0/4+1 | | 3(2x-5)=x-45 | | 4(4x-14)+x=5x-20 | | 5x+15=-3x-49 | | x/4-5=27 | | 3+4(n+2)=2n+3(n+4) | | x(x-15)=3(x-27) | | 0.67x+3.0=0.84x | | 23+2b=3(b+8)-3 | | 2(5x-4)=6x+12 | | -0/4+1= | | 5(5x-4)=-9x+2 | | -4y-2(4-3y)=3(y-4) | | 8(x+4)+5=101 | | 5x-2(3+x)=2(x+2) | | -6x-8+2=4x+20 | | 2(5)(3)= | | 2(x-9)+12=19 | | 2xy+7xy+5xy= | | 3(5x+2)-x=2(x-3) | | 3X=9X+3 | | -5/11+5/22= |